Pacemaker Syndrome. Case report. - Brandy Viera Valdés (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Pacemaker Syndrome is a clinical entity, most frequently produced by an inadequate AV synchrony, in which the phenomenom of retrograde AV conduction plays a major role, generally in patients with a single-chamber pacemaker with a WI stimulation mode. Main symptoms are: syncope, severe blood hypotension and congestive heart failure. The treatment, both prophylactic and therapeutical, would be related to the appropriate choice of stimulation mode, starting from individual analysis of each patient. We present a case of a patient with pacemaker syndrome, whose primary symptom was syncope on small physical activity, which made him unable to perform ordinary activities. The solution to the problem was substitution of single-chamber stimulation mode by a dual-chamber DDDR system, new surgery and placing of a electrode being necessary.